[quote=radioflyer01;38585]Please solve and explain how these are solved.
[\quote]
The steps should be fairly transparent:
$\displaystyle \frac{x}{6} - (-10) = 3$
$\displaystyle \frac{x}{6} + 10 = 3$
$\displaystyle \frac{x}{6} + 10 - 10 = 3 - 10$
$\displaystyle \frac{x}{6} = -7$
$\displaystyle 6 \cdot \frac{x}{6} = 6 \cdot (-7)$
$\displaystyle x = -42$
-Dan
Well, I was kinda hoping you'd show me how you did it so I could point out where you were right and, perhaps, where you went wrong.
$\displaystyle 30 + y = -10$
We need to get y by itself, so I'm going to take away 30 from the RHS. Thus I also have to take away 30 from the LHS:
$\displaystyle 30 + y - 30 = -10 - 30$
$\displaystyle y = -40$
-Dan